Effectiveness of Educational Intervention on Knowledge Regarding Newborn Care among Nurses Working in Maternity Units of B. P. Koirala Institute of Health Sciences, Nepal - Rai, Gayatri; Shrestha, Mangala; Pokharel, Nirmala; Bhandari, Sunita (International Journal of Nursing Research, 2023)
Introduction: Globally, 2.5 million children died in the 1st month of life in 2017. An estimated 23,000 children die in Nepal each year before reaching their fifth birthday with three out of five babies dying within 28 days after birth. Children who die within the first 28 days of birth suffer from conditions and diseases associated with lack of quality care at birth or skilled care and treatment immediately after birth and in the 1st day of life. Objective: The objective of the study was to assess the effectiveness of educational intervention about newborn care among nurses. Materials and Methods: A pre-experimental one-group pretest-posttest design was employed in the study. Fortyfour nurses working in maternity units of B. P. Koirala Institute of Health Sciences were selected through convenient sampling method. A pre-tested structured self-administered questionnaire was used to collect the data. Frequency, percentage, mean, standard deviation, Chi-squared test, and Spearmen correlation were used to analyze the data. Results: The findings showed that most of the knowledge lacking areas in pretest were cord care, temperature of birth room, first sponge bath, and second follow-up visit for newborn care. The mean±SD knowledge scores were 21.93±7.20 and 33.68±4.31 in pre-test and post-test, respectively. The pre-test and post-test knowledge scores were positively correlated (rs =0.136). Conclusion: The findings indicated that educational intervention was effective for enhancing nurses’ knowledge of newborn care. Continue nursing education and training for nurses would be beneficial to increase nurses’ knowledge on newborn care.